Pengaruh Terapi Bermain Menggambar Terhadap Kecemasan Hospitalisasi Pada Anak Usia Sekolah (6-12 Tahun) - Luckita Sari, Anggi; Santi, Prita Onita; Istiqomah, Nurul; Purwaningsih, Heni (TRIAGE Jurnal Ilmu Keperawatan, 2024)
Caring for children in hospital is an experience full of stress, both for children and parents. Hospitalization will create a series of traumatic events and anxiety in the parents' uncertainty. Anxiety is a feeling of worry or discomfort as if something is happening which is perceived as a threat, and is a daily experience experienced by individuals. Drawing play therapy is an alternative that can be used to increase stimulation and reduce anxiety due to hospitalization during inpatient care. This study aims to determine the effect of drawing play therapy on hospitalization anxiety in school-aged children (6-12 years) in the inpatient pediatric ward of PKU Muhammadiyah Sukoharjo Hospital. This type of research is quantitative research using a One Group Pre-Post Test Design. The sampling technique used purposive sampling with a sample size of 30 respondents. The data collection tool uses a questionnaire sheet and the data is analyzed using the Wilcoxon Test. The results of the Wilcoxon test showed a p-value = 0.000 < 0.05, meaning that there was an effect of play therapy on reducing anxiety in children treated in the children's ward of PKU Muhammadiyah Sukoharjo Hospital. Providing play therapy has a significant change in reducing children's anxiety after being given play therapy.